Long-Term Biased β-Arrestin Signaling Improves Cardiac Structure and Function in Dilated Cardiomyopathy. Issue 11 (14th March 2017) - Ryba, David M.; Li, Jieli; Cowan, Conrad L.; Russell, Brenda; Wolska, Beata M.; Solaro, R. John
Abstract : Background: Biased agonism of the angiotensin II receptor is known to promote cardiac contractility. Our laboratory indicated that these effects may be attributable to changes at the level of the myofilaments. However, these signaling mechanisms remain unknown. Because a common finding in dilated cardiomyopathy is a reduction in the myofilament-Ca 2 + response, we hypothesized that β-arrestin signaling would increase myofilament-Ca 2 + responsiveness in a model of familial dilated cardiomyopathy and improve cardiac function and morphology. Methods: We treated a dilated cardiomyopathy–linked mouse model expressing a mutant tropomyosin (Tm-E54K) for 3 months with either TRV120067, a β-arrestin 2–biased ligand of the angiotensin II receptor, or losartan, an angiotensin II receptor blocker. At the end of the treatment protocol, we assessed cardiac function using echocardiography, the myofilament-Ca 2 + response of detergent-extracted fiber bundles, and used proteomic approaches to understand changes in posttranslational modifications of proteins that may explain functional changes. We also assessed signaling pathways altered in vivo and by using isolated myocytes. Results: TRV120067- treated Tm-E54K mice showed improved cardiac structure and function, whereas losartan-treated mice had no improvement. Myofilaments of TRV120067-treated Tm-E54K mice had significantly improved myofilament-Ca 2 + responsiveness, which was depressed in untreated Tm-E54K mice. We attributed these changes to increased MLC2v and MYPT1/2 phosphorylation seen only in TRV120067-treated mice. We found that the functional changes were attributable to an activation of ERK1/2-RSK3 signaling, mediated through β-arrestin, which may have a novel role in increasing MLC2v phosphorylation through a previously unrecognized interaction of β-arrestin localized to the sarcomere. Conclusions: Long-term β-arrestin 2–biased agonism of the angiotensin II receptor may be a viable approach to the treatment of dilated cardiomyopathy by not only preventing maladaptive signaling, but also improving cardiac function by altering the myofilament-Ca 2 + response via β-arrestin signaling pathways. Abstract : Supplemental Digital Content is available in the text.